Evaluating transport of Cu in agricultural soils under sewage irrigation - ZHENG Shun-an; LI Yi; PU Jin-cheng; ZHANG Ming-kui (浙江大学学报. 农业与生命科学版)
To obtain the knowledge of impact of sewage irrigation on soil, crops and shallow groundwater, soil column experiment was conducted to assess the transport behaviors of Cu in 7 typical Chinese agricultural soils under sewage irrigation. Soil columns were leached with artificial sewage irrigation water (Cu 20 mg·L-1) accounting for 20 L. The Hydrus-1D was used for fitting the breakthrough curves of Cu. The results manifested that, the studied black soil, yellow fluvo-aquic soil and loessial soil had great adsorption capacity for Cu, resulting in that the leachate concentrations of Cu did not exceed the value on the groundwater quality standards Ⅱ; on the other hand, the studied red soil, grey fluvo-aquic soil, two kinds of paddy soils did not had strong adsorption capacity for Cu, making Cu could rapidly breakthrough the soils, and presented potential pollution risk for groundwater or environment. The analysis of Hydrus-1D indicated that, the transportation of Cu in black soil, yellow fluvo-aquic soil and loessial soil under sewage irrigation could be well described by deterministic equilibrium model, while the transportation of Cu in red soil, gray fluvo-aquic soil and two kinds of paddy soils could be well simulated by two-site model. It was found that, the adsorption capacity of Cu in soils was the key factor to control the entire process of transportation of Cu.